Interaction Between Plant Competition and Rhizospheric Bacterial Community Influence Secondary Succession of Abandoned Farmland on the Loess Plateau of China - Sun, Caili; Liu, Guobin; Xue, Sha (Frontiers in Plant Science, 2018)
Interactions between plant and soil have important implication for plant competition, development and succession. In order to explore the internal mechanism behind natural succession of abandoned farmland, we test the effect of plant-soil interaction on plant growth and competitive ability through performing a pot experiment, which included three grasses in different successional stages on the Loess Plateau of China (Setaria viridis, Stipa bungeana and Bothriochloa ischaemum) in monoculture and all possible two- and three-way combinations, along with a plant-free control pot. The plants were harvested after about four months, and the rhizospheric soil was collected. The bacterial communities of the soils were analyzed by high-throughput sequencing of the 16S rRNA gene. Plant competition affected richness of bacterial communities. Proteobacteria and Bacteroidetes were generally higher and Actinobacteria and Acidobacteria were lower in relative abundance in the mixed treatments associated with B. ischaemum. Photosynthetic bacterium, Genus Rhodobacter family Rhodospirillaceae, affected the growth condition and increased the competitive ability of B. ischaemum. Differences in the amounts of soil organic carbon, water-soluble organic carbon and nitrate nitrogen and available phosphorus drove the differences in bacterial communities. Our study has an important significance for understanding the trend of natural succession on the abandoned farmland on the Loess Plateau of China.